Coleridge and the Lay Sermon. Issue 7 (3rd October 2017) - During, Simon; O'Connell, Lisa
ABSTRACT: This essay, a contribution to the study of secularisation, explores conditions under which a new genre, the lay sermon, emerged early in the nineteenth century. It does so through a reading of the texts that inaugurate the genre, Samuel Taylor Coleridge's Lay Sermons (1817). In particular, the essay examines Coleridge's Lay Sermons ' historical context, that is, to the beginnings of liberal politics. And it also pays attention to Coleridge's relation to the heritage of religious sermons, especially seventeenth- century sermons. It argues that the lay sermon, unlike the religious sermon, tends to be directed to particular social groups or formations rather than, more broadly, to Christians of a particular denomination.